Entrepreneurship, dyslexia, and education : research, principles and practice - Pavey, Barbara; Alexander-Passe, Neil; Meehan, Margaret (New York, NY : Routledge, 2021)
"The development of entrepreneurial abilities in people with dyslexia is a subject of great interest. It has gained increasing importance in economically difficult times because of its potential for the development of new business opportunities. This book brings together contributions from researchers, educators, and entrepreneurs with dyslexia, investigating this subject from many perspectives. Is there something different in the profile of a person with dyslexia, that supports the development of entrepreneurship? This book aims to draw out key themes which can be used in education to motivate, mentor and create the business leaders of tomorrow. It offers a fundamental text for this area of study with a comprehensive, international examination of its topic. It includes views by new and established international writers and researchers, providing up-to-date perspectives on entrepreneurship, dyslexia and education. It is accessible to read, to understand and to learn from, and is suitable for recommended reading for graduate and postgraduate students. The diverse views and perspectives demonstrated in this book make it as relevant as possible for a wide group of readers. It informs study in the fields of business and dyslexia, and will be of interest to educators, researchers and to anyone interested in the overlap of entrepreneurship and dyslexia"--
OCLC-licensed vendor bibliographic record.
Keywords: Entrepreneurship; Dyslexics -- Intellectual life; BUSINESS & ECONOMICS / Entrepreneurship; BUSINESS & ECONOMICS / Management; BUSINESS & ECONOMICS / Leadership